The Correlation of Decreased E-Cadherin and Î²1-Integrin Expression with the Depth of Myometrial Invasion and Pelvic Lymph Node Metastasis in Resectable Endometrial Cancer - Hasanuddin Hasanuddin (Indonesian Socety of Obstetrics and Gynecology, 2010)
Objective: The purpose of this study was to determine the correlation between decreased E-Cadherin and Î²1-integrin expression in resectable endometrial cancer with the depth of myometrial invasion and pelvic lymph node metastasis. Method: This was a cross sectional study, we used immunohistochemistry examination on E-Cadherin and Î²1-integrin expression in resectable endometrial cancer patients who had surgery in 1997 to 2006 in Dr. Cipto Mangunkusumo Hospital and searched the correlation with the depth of myometrial invasion and pelvic lymph node metastasis. Result: The prevalence of endometrial cancer from 1997 to 2006 in Dr. Cipto Mangunkusumo Hospital was 7.0 in a year. Out of 64 patients with endometrial cancer only 36 paraffin block could be found and immunostaining on E-Cadherin and Î²1-integrin was done in 30 samples. Decreased E-Cadherin and Î²1-integrin expression was associated with the depth of myometrial invasion, pelvic lymph node metastasis, lymph ovascular space involvement and degree of differentiation in resectable endometrial cancer patients. Conclusion: Decreased E-Cadherin and Î²1-integrin expression was associated with the depth of myometrial invasion and pelvic lymph nodes metastasis. [Indones J Obstet Gynecol 2010; 34-3: 136-42] Keywords: E-Cadherin, Î²1-integrin, the depth of myometrial invasion, pelvic lymph node metastasis